2012
DOI: 10.1021/ol302096j
|View full text |Cite
|
Sign up to set email alerts
|

Method for the Efficient Synthesis of Highly-Substituted Oxetan- and Azetidin-, Dihydrofuran- and Pyrrolidin-3-ones and Its Application to the Synthesis of (±)-Pseudodeflectusin

Abstract: Highly substituted four- and five-membered heterocycles were prepared starting with O,P- and N,P-acetals by using a one-pot method involving base induced cyclization and a Horner-Wadsworth-Emmons (HWE) olefination reaction. Divergent synthesis of various heterocycles was achieved by using this method and transformations of the alkenyl group in the products of these processes were exemplified. Finally, a short and efficient synthesis of (±)-pseudodeflectusin based on the new methodology was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…88) Recently, Fujioka et al reported the synthesis of (AE)-42 starting with an O,P-acetal using a one-pot method involving base-induced cyclization and the Horner-Emmons reaction. 89) We started the synthesis of pseudodeflectusin and ustusorane C from tert-butylbenzamide 46.…”
Section: Synthesis Of Pseudodeflectusin and Ustusorane Cmentioning
confidence: 99%
“…88) Recently, Fujioka et al reported the synthesis of (AE)-42 starting with an O,P-acetal using a one-pot method involving base-induced cyclization and the Horner-Emmons reaction. 89) We started the synthesis of pseudodeflectusin and ustusorane C from tert-butylbenzamide 46.…”
Section: Synthesis Of Pseudodeflectusin and Ustusorane Cmentioning
confidence: 99%
“…16 TBS protection of the newly installed alcohol functionality was markedly slow and low yielding. Protection of the secondary alcohols 18a and 18b with MOMCl 17 was also slow at room temperature. Microwave irradiation conditions at 80 °C for 10 minutes, however, succesfully yielded the desired MOM protected alcohols.…”
mentioning
confidence: 99%
“…In continuation of Fujioka's interest in the chemistry of acetals [34], the synthesis of highly substituted azitidines 23 from O,P-acetals 21 was described through a one-pot protocol [35]. A number of trials were undertaken for the 23 (yield up to 81%) R 1 , R 2 = CH 3 , -(CH 2 ) 5 -; R 3 =Ph, 4-OCH 3 Ph Scheme 8 Azitidines from O,P-acetals base-mediated cyclization of O,P-acetals 21 to furnish intermediate phosphono-oxetanone which was not isolated.…”
Section: Synthesis Of Azitidinementioning
confidence: 99%